2019
DOI: 10.12669/pjms.35.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Why doctors are not satisfied with their job current status in tertiary care hospitals

Abstract: Objective: To determine level and factors of job satisfaction among doctors working in tertiary care hospitals in Pakistan. Methods: This is a multi-center cross-sectional survey conducted among Post graduate trainees, medical officers, consultants and faculty doctors. Job satisfaction was measured using 35 specific questions about sources of work-related stress and sources of work-related satisfaction. Satisfaction was defined if mean score of a factor was ≥3.0, where factors were rated using a 5-point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Job dissatisfaction was more amongst government sector doctors; whereas, increasing age, duration of current posting and work experience positively correlated with satisfaction level. 30 There are at least two other studies from Oman assessing job satisfaction of physicians. Al Shafaee 18 used qualitative and quantitative tools to assess job satisfaction amongst physicians working in the capital area, Muscat governorate, and explored several organizational and jobrelated factors which influence satisfaction rate.…”
Section: Discussionmentioning
confidence: 99%
“…Job dissatisfaction was more amongst government sector doctors; whereas, increasing age, duration of current posting and work experience positively correlated with satisfaction level. 30 There are at least two other studies from Oman assessing job satisfaction of physicians. Al Shafaee 18 used qualitative and quantitative tools to assess job satisfaction amongst physicians working in the capital area, Muscat governorate, and explored several organizational and jobrelated factors which influence satisfaction rate.…”
Section: Discussionmentioning
confidence: 99%
“…7,15 In Pakistan, registrars were also found to be more dissatisfied with their current job status because of the stressful nature of their job. 26 This is worrisome as it has been documented that the greater the doctor's dissatisfaction is, the greater the level of stress and tendency towards an increased turnover. 16,27 On the contrary, a study conducted in Kaduna State, Nigeria showed a disproportionately higher level of job satisfaction (80.1%) among the resident doctors.…”
Section: Discussionmentioning
confidence: 99%
“…La evidencia científica internacional demuestra que los estudios de egresados sirven para fortalecer los servicios para la sociedad, en materia de educación permiten a los estudiantes identificar las fortalezas y debilidades percibidas del programa educativo estudiado de acuerdo a las necesidades en el área laboral (Soboka et ál., 2018), además del efecto de la insatisfacción con el salario, entorno laboral, carga de trabajo, seguridad y equilibrio familiar y laboral sobre calidad en el desempeño profesional (Ali, Zuberi, Rasheed y Shaikh, 2019).…”
Section: Marco Referencial De Los Estudios De Egresadosunclassified